Improvement of Solubility Usnic Acid Loaded on Mesoporous Silica SBA-15 and Physicochemical Characterization - Fitriani, Lili; Azzahra, Cindy Maynia; Jessica, Adhitya; Hasanah, Uswatul; Zaini, Erizal (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Usnic acid, a secondary metabolite of lichen Usnea sp., has several pharmacological activities, but it is poorly soluble in water. This study aimed to improve the solubility and dissolution rate of usnic acid loaded in mesoporous silica SBA-15 at a mass ratio of 1:1. and evaluate its physical stability. Physicochemical characterization was carried out via the nitrogen adsorption desorption isotherm, differential scanning calorimetry (DSC), Fourier transform infrared (FTIR) spectroscopy, and powder X-ray diffraction (PXRD). Usnic acid-loaded SBA-15 was stored at 40 °C with various relative humidities (RH) and then analyzed by PXRD for the physical stability. Usnic acid adsorbed well in the pores of SBA-15, as shown by a decrease in the volume pore and surface area of SBA-15 according to the nitrogen adsorption. Moreover, usnic acid-SBA-15 showed a decrease in the degree of crystallinity according to PXRD analysis and no melting point based on DSC analysis. The FTIR spectrum of usnic acid–SBA-15 corresponds to the spectra of each raw material. The solubility of usnic acid increased 5.15 times after adsorbed on SBA-15. The dissolution rate also showed a significant increase (p < 0.05) from 19.51% to 84.27%. Usnic acid–SBA-15 was relatively stable at RH 75%. Thus, the adsorption of usnic acid on SBA-15 can increase its solubility, dissolution rate, and physical stability.